Journalism and Mass Communication.Educator. (Columbia,SC: Association for Educationin Journalism and Mass Communication in Cooperation with Association of schools of Journalism and Mass Communication.)
Covers Media and Culture which is the groundbreaking introduction to mass communication text that uses a unique critical approach and cultural perspctive to help stundents understand the dynamics of mass media.